Patients’ perception on quality of care for prostate cancer at tertiary hospitals in Tanzania: a qualitative study - Nyongole, Obadia; Kakoko, Deodatus; Sirili, Nathanael; Frumence, Gasto; Simba, Daudi; Urassa, David; Sunguya, Bruno (Frontiers in Oncology, 2024)
BackgroundProstate cancer is a common cancer among men globally and its treatment affects quality of life. Poor patients’ perception of prostate cancer services may lead to their late presentation for care, often presenting with the advanced stage of the disease. This may vary from one region to another.ObjectiveThis study, therefore, aimed to explore patients’ perceptions of the quality of care for prostate cancer in Tanzania.MethodsThis qualitative case study was conducted in five tertiary hospitals in Tanzania in November 2023. In-depth interviews were conducted with prostate cancer patients on treatment for not less than 6 months. Data on patients’ perception of prostate cancer, quality of prostate cancer services, and quality of life among prostate cancer patients were collected. Thematic analysis used a hybrid inductive and deductive reasoning approach through NVivo 14 software.ResultsA total of 17 interviews were conducted, resulting in four themes. These were perception of prostate cancer on the causes and diagnostic methods, delays of care leading to late presentation, perception of quality of life after treatment for prostate cancer recovery versus cancer progression, and quality of service in terms of organization of service delivery for prostate cancer at tertiary hospitals in Tanzania.ConclusionQuality of services for prostate cancer was well-perceived, especially communication for psychosocial support. A good perception of the quality of service was found to influence the uptake of prostate cancer services. Prostate cancer patients have mixed perceptions about the quality of life after treatment, which delays health seeking, leading to late presentation. Despite efforts in awareness campaigns through different platforms, more effort is needed in determining the causes of prostate cancer, the diagnostic/screening methods necessary for prostate cancer, timely health seeking, the available treatment options for prostate cancer, and the expected quality of life after treatment.